Novel Composite Approximation for the Gaussian Q-Function - Peric, Zoran H.; Markovic, Aleksandar V.; Kontrec, Natasa Z.; Panic, Stefan R.; Spalević, Petar C. (Elektronika ir Elektrotechnika, 2020)
This paper, by using Borjesson’s and Benitez’s approximation of Q-function, presents a novel and improved composite approximation of Q-function with wide applicability. The presented approach is very general and can be implemented on any observed interval. Based on the proposed approximation of Q-function, the average bit error rate is assessed by observing the transfer over Nakagami-m fading channel. The simplicity of the proposed approximation form in conjunction with yet another feature - utmost accurateness - appeared to be a better choice than the suggested approximations of similar complexity in terms of analyticity. The paper emphasizes the wide implementation possibilities in numerous tasks of communication theory and functional analysis that include Q-function.